The effectiveness of the SAVI method in improving poetry reading skills of elementary students - Abdul Latif; Septia Sugiarsih; Anwar Novianto (Jurnal Penelitian Ilmu Pendidikan, 2025)
This study examines the effectiveness of the Somatic, Auditory, Visual, Intellectual (SAVI) learning method in enhancing the poetry reading skills of fifth-grade elementary school students. Employing a quantitative approach with a one-group pretest-posttest design, the research involved 36 fifth-grade students from Muhammadiyah Condongcatur Elementary School. Data were collected through structured observation sheets and analyzed using a paired sample t-test. The results indicate a statistically significant improvement in students' poetry reading skills following the intervention, with a significance value of 0.001 (< 0.05). The mean score increased by 30.72 points from pretest to posttest, demonstrating a substantial gain in performance. These findings lead to the conclusion that the SAVI method is an effective instructional strategy for significantly improving poetry reading proficiency in the target student population.